FUTURE FOR AIRLINEâ€™S VOLUNTARY CARBON OFFSETS IN MALAYSIA - Fatin Farazh Yaâ€™acob; Abdullah Mohamad; Nur Fatihah Shaari; Nur Amalina Aziz; Muhammad Majid; Mohamad Faizal Ramli (Journal of Islamic, Social, Economics and Development, 2022)
In the past decade, voluntary carbon offsetting has gained popularity, particularly among airlines, to â€œneutralizeâ€ emissions associated with travel. Although there are various carbon offsetting programmes offered by the airline industry worldwide, none of them is implemented in Malaysia. Despite this, few studies have examined the willingness of participation among Malaysian airline passengers voluntarily engage in carbon offsetting. The purpose of this study is to investigate the future of airline carbon offset in Malaysia by looking at the response from the respondent regarding their knowledge and experience of carbon offset. Findings show that Malaysian airline passengers are willing and accept airline carbon offset as one of the methods to reduce the emissions from their travelling. Our results are useful for airlines to design voluntary proposals, improve the corporate image, and for policymakers to support air travellersâ€™ environmentally conscious behaviour and airlinesâ€™ environmentally sustainable strategies. Consequently, this may suggest that social marketing, public discourse, and extensive media coverage in Malaysia must increase climate change mitigation behaviours among Malaysian airline travellers.